Thermal and Morphological Properties of Organo Modified Nanoclay/Polyethylene Terephthalate Composites - KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (SPRINGER, 2017)
The purpose of this study is polyethylene terephthalate (PET) and modified organo-nanoclay with different masses and to contribute to the different areas of use and literature by examining these nanocomposites physical, chemical and thermal features. In this study, nanocomposite films, which work in PET that is a type of polymeric material, and work into modified organo-nanoclays with different percentages, obtained with the method called as in situ polymerization. The chemical structures of nanocomposites prepared were investigated by fourier transform infrared spectroscopy. The surface morphologies of this nanocomposites were examined by scanning electron microscope. Their thermal properties were analyzed by differential scanning calorimetry and thermogravimetric analysis. According to the results obtained, the thermal stabilities of modified nanoclay composites got better than PET. Besides, while the percent of clay in the doped PET was rising, its fragility increased. At the same time, high mass of clay formed when the percent of contribution developed. Thus, the surface interaction of polymer-clay decreased, because the composed aggregations prevented the polymer matrix from going into the layer of clay.
Keywords: Polyethylene terephthalate; Organo modified nanoclay; Composites; NANOCOMPOSITES; POLY(ETHYLENE-TEREPHTHALATE)